THE REALITY OF FOOD INSECURITY AMONG UNIVERSITY STUDENTS: A LITERATURE REVIEW - Norzuraida Hasan,; Asiah Kamal,; Zanirah Mustapha@Busu,; Nurul Izzah Noor Zainan, (Journal of Islamic, Social, Economics and Development, 2023)
Food insecurity (FI) exists whenever people are unable to access sufficient food at all times for an active and healthy life. University students are a potentially vulnerable group of people to face food insecurity. This article reviews the literature on food insecurity among university students, by focusing on the aspects of the level of food insecurity, the factors that cause food insecurity and the impact of food insecurity on students. This study is a qualitative study which collects data through library research as well as content analysis of articles related to the lack of food security among university students around the world. The literature reviews conducted revealed that there are various levels of food insecurity among students at various universities due to various factors including the increase in the cost of living, the increase in tuition fees and the lack of financial aid which causes them not only to be exposed to a situation of food insecurity but negatively impacts their academic performance.